Intravitreal injection of aflibercept, an anti-VEGF antagonist, down-regulates plasma von Willebrand factor in patients with age-related macular degeneration - Mariko Yamashita (Nature Portfolio, 2018)
Abstract We investigated the association between von Willebrand factor (VWF) and exudative age-related macular degeneration (AMD) in 114 Japanese patients. Intravitreal injection of vascular endothelial growth factor (VEGF) inhibitor is the most effective therapy for AMD. Therefore, we analyzed changes of VWF antigen (VWF:Ag) and VWF multimers (VWFMs) after intravitreal injection of aflibercept, an anti-VEGF antagonist. The relationship between polymorphisms in complement factor H (p.Y402H and p.I62V) and AMD was previously reported. In our patients, p.I62V, but not p.Y402H, was significantly associated with an increased risk of AMD. Pre-treatment plasma levels of VWF:Ag in patients with AMD were significantly higher than those in controls. Unusually large VWFMs (UL-VWFMs) were detected in the majority of AMD patients with concurrent vitreous or subretinal hemorrhage. After intravitreal injection of aflibercept, plasma levels of VWF:Ag and VEGF-A were significantly decreased. UL-VWFMs disappeared after aflibercept injection in three cases, but persisted even 1 month after injection in the other five cases. In conclusion, plasma VWF:Ag levels were significantly elevated in patients with AMD, and decreased after intravitreal aflibercept injection. VWF may play an important role in the pathophysiology of AMD, and aflibercept might improve AMD by reducing plasma levels of VWF in addition to VEGF-A.